Gaya Hidup dan Pola Makan Terhadap Kejadian Hipertensi - Yessi Aprillia (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2020)
Hypertension or high blood pressure is a type of non-communicable disease that is chronic and can cause complications in body organs such as the heart, kidney, brain, and eyes. Hypertension can cause blood pressure to rise beyond normal limits. In systolic blood pressure hypertension it can reach ≥ 140 mmHg and diastolic blood pressure ≥ 90 mmHg. The purpose of this study is to know the lifestyle and diet that can be used to prevent hypertension. The analytical method used is through a literature review that contains a description of the theory, the results of previous studies with the focus of the appropriate and relevant topics. Library studies used are 20 articles from 2015 to 2020 with search using 1 database, namely Google Scholar. Keywords used include lifestyle, diet and hypertension. The results of previous studies showed a relationship between the lifestyles and diet of the incidence of hypertension